2021
DOI: 10.1021/acs.est.1c00308
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Guidance for Environmental Scientists Engaged in Surveillance of Wastewater for SARS-CoV-2

Abstract: The COVID-19 pandemic has given rise to rapid and widespread international pursuit of wastewater surveillance for genetic signals of SARS-CoV-2, the virus causing the pandemic. Environmental scientists and engineers familiar with the techniques required for this endeavor have responded. Many of the environmental scientists engaged in these investigations have not necessarily had experience with the ethical obligations associated with generating and handling human health data. The Canadian Water Network facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 28 publications
(39 reference statements)
0
37
0
1
Order By: Relevance
“…Although there is general agreement about the desirability of having standardized sampling and analytical protocols, it has not been possible to implement such standardization while simultaneously performing WBS during the course of the pandemic. Chik et al (2021) reported on an interlaboratory study among eight laboratories organized by the CWN. Wastewater from the City of Winnipeg, at a time when it had only 85 known cases in a total population of 700,000 (1.2 cases per 10,000), was provided as a blank.…”
Section: Representativeness Of Samples and Analytical Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although there is general agreement about the desirability of having standardized sampling and analytical protocols, it has not been possible to implement such standardization while simultaneously performing WBS during the course of the pandemic. Chik et al (2021) reported on an interlaboratory study among eight laboratories organized by the CWN. Wastewater from the City of Winnipeg, at a time when it had only 85 known cases in a total population of 700,000 (1.2 cases per 10,000), was provided as a blank.…”
Section: Representativeness Of Samples and Analytical Resultsmentioning
confidence: 99%
“…In lieu of the development of a single standardized method for WBS for SARS-CoV-2, there is a clear need for the development of standardized quality assurance and quality control (QA/QC) requirements that can streamline the approach to the evaluation of the various methods, improving confidence in the reliability of the analytical results from the different methods and making more useful and reliable any comparisons between different sites or laboratories. Gawlik et al (2021) have called for developing a QA/QC framework, noted that the EU is committed to implementing a proficiency test and called for more interlaboratory testing such as reported by Chik et al (2021). The establishment of standardized QA/QC requirements should significantly improve the basis for greater confidence in the use of the analytical data for public health applications going forward.…”
Section: Variability Of Methods Used For Detecting Sars-cov-2 In Wastewatermentioning
confidence: 99%
See 2 more Smart Citations
“…Despite these factors limiting wastewater surveillance, it holds tremendous potential as an inexpensive type of widespread monitoring that can detect hotspots before they turn into outbreaks, inform recovery guidance and avoid the emergence or resurgence of the SARS-CoV-2 [95]. Further efforts are required in the field, including policy reforms, ethical practices, sophisticated protocols useful for measuring virus concentrations in wastewater, and accurate estimation of disease prevalence and community surveillance [94,96].…”
Section: Wastewater-based Epidemiologymentioning
confidence: 99%